1994
DOI: 10.1111/j.1467-9582.1994.tb00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Word Order Variation, Verb Movement, and Economy Principles

Abstract: In Chomsky's Minimalist framework, word order variation reflects different movement options arising from interaction between parametrized morphological properties of functional items and invariant economy principles. In the simplest case, languages vary in whether a given movement (e.g. V-to-I-raising) feeds PF (French) or not (English). We consider more complex cases involving language-internal word order differences due to construction-specific movementGermanic Verb-Second, Last Resort Verb-fronting in Croat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…Chomsky (1993) proposed that movement must satisfy the needs of the category moved: so-called Greed. Wilder and Ć avar (1994) and Lasnik (1995) showed that there are cases where a movement appears to satisfy only the needs of the target (''Altruism'' or ''Enlightened Self-Interest''). In Chomsky 1995 movement is triggered by the needs of the target only (Attract).…”
Section: * (Icelandic)mentioning
confidence: 97%
“…Chomsky (1993) proposed that movement must satisfy the needs of the category moved: so-called Greed. Wilder and Ć avar (1994) and Lasnik (1995) showed that there are cases where a movement appears to satisfy only the needs of the target (''Altruism'' or ''Enlightened Self-Interest''). In Chomsky 1995 movement is triggered by the needs of the target only (Attract).…”
Section: * (Icelandic)mentioning
confidence: 97%
“…Wilder & Cavar 1994). It must also then be ensured that specCP is not filled by some other category, for instance a wh-phrase, since, just as in the case of phrasal topicalization, the fronted, contrastively focused verb cannot be preceded by any category.…”
Section: (37) [T [Agro [Have [Neg [Su [V Ob]]]]]]mentioning
confidence: 98%
“…I do not pursue this problem here, since it is beyond the scope of the article. See also Wilder and Ć avar 1993, Wexler 1994, and Vikner 1995 for discussion of auxiliary movement. 7 See Brody 1995 for a similar proposal for infinitives in Hungarian.…”
Section: The Head Movement Hypothesis and The Distribution Of The Negmentioning
confidence: 97%